Problem-Based Learning (PBL), review of the topic in the context of health education - Gonzalez-Argote, Javier; Castillo-González, William (Seminars in Medical Writing and Education, 2024)
Introduction: Active methodologies promote learning through the resolution of real situations, promoting the construction of knowledge and skills. This turns the student into an active participant, strengthening their critical thinking skills. A bibliographic review was carried out with the objective of reviewing the problem-based learning method and its benefits in the context of medical education.Methods: a bibliographic review was carried out between December 2023 and January 2024 in the main databases and other search services. The terms “problem-based learning”, “health education”, “medical education” were used as search descriptors.Results: In medical education, the problem-based learning approach focuses on students addressing real clinical situations to develop diagnostic and therapeutic skills. This model seeks to ensure that, from the beginning of their training, future health professionals are involved in medical practice, instead of only acquiring theoretical knowledge. The development of critical thinking is essential to face real-world clinical situations, so learning must be student-centered and meaningful, involving problems that reflect real contexts of professional practice.Conclusions: Problem-based learning is one more strategy in the wide range of possibilities for teaching and developing medical education, and it has advantages and disadvantages like any other strategy.